Hepatitis C virus infection with peripheral neuropathy is not always associated with cryoglobulinaemia. Issue 3 (1st March 2001) - Lidove, O; Cacoub, P; Maisonobe, T; Servan, J; Thibault, V; Piette, J-C; Léger, J-M
Abstract : OBJECTIVES: To describe cases of peripheral neuropathy associated with chronic hepatitis C virus infection without mixed cryoglobulinaemia. METHODS: Four cases of peripheral neuropathy associated with chronic hepatitis C virus infection with persistent negativity of mixed cryoglobulinaemia were found. RESULTS: All patients had small increases of transaminase levels and a positive viraemia. Liver biopsy showed chronic active hepatitis in all but one case (Knodell 4–9, Metavir A0F0-A3F3). Neuromuscular biopsy showed axonal neuropathy associated with lymphoid infiltrates around small vessels in two cases. Rheumatoid factor was always negative and C4 complement level was always normal. In three patients, neuropathy improved with interferon α, interferon α + ursodesoxycholic acid, or steroids + plasma exchange. CONCLUSION: Peripheral neuropathy may be associated with hepatitis C virus infection without mixed cryoglobulinaemia.